"I Have the Government in My Pocket…": Social Media Users in Turkey, Transmit-Trap Dynamics, and Struggles Over Internet Freedom. (30th August 2017) - Parks, Lisa; Goodwin, Hannah; Han, Lisa
Abstract: This article explores how social media users in Turkey conceptualize and navigate free speech challenges in the wake of recent government crackdowns on media institutions. The study is based on qualitative interviews with 40 social media users in Istanbul, including people from LGBTQ, feminist, Kurdish, journalist, activist, and academic communities, who have been on the front lines of free speech struggles in Turkey. Informants' comments converged around a theme of transmit-trap dynamics, which emphasizes user experiences in the context of "networked authoritarianism, " and speaks to the ways Turkish social media users find themselves simultaneously empowered by and targeted within social media platforms.